Identificação de novos antígenos de espécies do gênero Leishmania com potencial uso no diagnóstico sorológico da leishmaniose visceral - Ana Luiza Teixeira Silva (2017)
Advances seeking a more efficient diagnosis of visceral leishmaniasis are still necessary, since this disease can be fatal if untreated. Despite the continuous development of immunodiagnostic tests, intrinsic limitations of each technique usually lead to an uncertain diagnosis. Over the last years, our group has been focused in immunogenomic studies for the search of new antigen candidates that would be more sensitive and specific. Using data mining methodologies, it is possible to identify proteins or peptides present in the parasites with homology to host molecules associated with the immune response, which may be the differential approach in an attempt to improve the performance diagnostic tests. In this context, the present study identified and tested three Leishmania proteins that present similarity to proteins present in the ImmunomeBase database, which comprises Homo sapiens proteins with biological function associated with previously characterized host defense processes. It was selected genes coding for ATP diphosphohydrolase protein of the Leishmania. infantum (EctoLi), GTP binding protein of the L. infantum (MyxoLi) and L. mexicana (MyxoLm), and tyrosine phosphatase protein of the L. braziliensis (TyroLb). These targets were expressed in a heterologous system using the plasmid pET28a-TEV as vector and Escherichia coli strain BL21 and Arctic Express as the expression system. After purification by affinity chromatography, the proteins were used as antigens in the ELISA test for human visceral leishmaniasis (HVL) and canine (CVL). The antigenic properties of the proteins were evaluated and the linear B-cell epitopes derived from these targets were identified. When proteins were tested with the dog sera, the efficiency of the test was able to discriminate the positive from the negative samples and the quality of the tests with the recombinant antigens, based on the area under the ROC curve, was between good and excellent, suggesting the use of these proteins for an initial screening of the animals and/or confirmatory test for CVL. In particular, EctoLi and MyxoLi showed high specificity, being useful not only to determine true positives and true negatives, but also to distinguish cross-reactions. The positive predictive value and the accuracy for the assays using these proteins were higher when compared to the EIE-LVC kit – Bio-Manguinhos, suggesting that the use of the antigens provides are better candidates for the diagnosis of LVC. When tested with human sera, the recombinant protein EctoLi demonstrated a good performance for diagnostic test screening and distinguished by the high specificity, being able to significantly separate infected from uninfected patients and with Chagas disease, suggesting to be a good candidate for HVL confirmatory test. In addition, the truncated protein MyxoTLm proved to be a good candidate for the serodiagnosis of trypanosomatids (Leishmania and Trypanosoma cruzi) with 100% specificity and 90% sensitivity, and our results suggest the possible use in blood bank screening. Taken together, our work suggests that the ELISA strategy based on recombinant proteins, homologous to the host immune system, could be an useful approach for the development of a more sensitive and specific tests for the serodiagnosis of this parasitosis.